Effects of clopidogrel, prasugrel and ticagrelor on prevention of stent thrombosis in patients underwent percutaneous coronary intervention: A network meta‐analysis. Issue 4 (11th March 2021) - Chen, Wenwen; Zhang, Chen; Zhao, Jian; Xu, Xiuxiu; Dang, Heqin; Xiao, Qiang; Li, Yuanmin; Hou, Haifeng
Abstract: Background: Clopidogrel, prasugrel and ticagrelor, acting on platelet P2Y12 receptor, are commonly used for prevention of stent thrombosis (ST) among patients who underwent percutaneous coronary intervention (PCI). This study aimed to compare the effects of these drugs by a systematic review and network meta‐analysis. Hypothesis: Efficacies of clopidogrel, prasugrel and ticagrelor on preventing ST are not the same. Methods: PubMed, Embase and Cochrane Library were searched for randomized controlled trials (RCTs) that investigated the effect of clopidogrel, prasugrel, or ticagrelor on prevention of ST in patients who underwent PCI. The efficacies between groups were compared by a Bayesian network meta‐analysis, by which the pooled odds ratios (ORs) and 95% confidence intervals (CIs) was calculated. Results: Fourteen studies and 46 983 participants were included in this study. The pooled results illustrated that clopidogrel, prasugrel and ticagrelor were effective on prevention of ST. Patients treated with prasugrel (OR = 0.30, 95% CI = 0.052 ~ 0.73, P < 0.05) and ticagrelor (OR = 0.25, 95% CI = 0.035 ~ 0.65, P < 0.05) had lower incidence of ST compared to those treated with clopidogrel. Patients treated with ticagrelor showed similar frequency with those in prasugrel group (OR = 0.86, 95% CI = 0.22 ~ 2.3, P > 0.05). No significant heterogeneity was observed across included studies. Conclusions: Our findings suggest that prasugrel and ticagrelor are more effective than clopidogrel on prevention of ST among patients underwent PCI. Simultaneously, there is no significant difference in the prevention of ST between prasugrel and ticagrelor.